Effectiveness of the Discrete Installation of Lightning Arresters on Transmission Lines - Ninh, Van Nam; Pham, Hong Thinh; Tran, Van Top (Old Journal, 2019)
Installation of lightning arresters on all phases of every tower theoretically eliminates the lightning outage of a transmission line. However, this measure has been found to be unaffordable due to its excessive cost. In practice, the so-called discrete installation of surge arrester in which arresters are installed in some selected towers is usually adopted. The effectiveness of this method remains questionable since the flashover still occurred in adjacent towers of the protected ones, which makes the outage rate unchanged even after installing surge arresters. This paper deals with the discrete installation of arresters in a 220 kV- one circuit transmission line. The influence of footing resistances, spans and the amplitude of lightning current on the tower position of flashover was investigated by using the Electromagnetic Transient Program (EMTP/ATP). The results can be used as a practical guide for the utilities to identify whether or not the discrete installation of arresters should be used in a specific tower.